Glycated Albumin and Glycemia in Pregnancy and Postpartum: A Pilot Study - Soffer, Marti D.; James, Kaitlyn E.; Thaweethai, Tanayott; Callahan, Michael; Barth, William H., Jr.; Powe, Camille E. (American Journal of Perinatology, 2023)
Objective Percent glycated albumin (%GAlb) is a marker of glycemia over the past 2 to 3 weeks in nonpregnant individuals. Longitudinal changes in %GAlb extending throughout pregnancy and postpartum (PP) have not been described. We aimed to describe levels of %GAlb throughout pregnancy and PP and relationships with glycemia.Study Design Fifty women among those in the Study of Pregnancy Regulation of INsulin and Glucose cohort underwent 75-g oral glucose tolerance tests (OGTTs) at a mean of 13 weeks (V1) and 26 weeks (V2) of gestation and 11 weeks' PP. %GAlb was measured on frozen plasma samples.Results Total albumin decreased from V1 to V2 and increased PP to levels higher than at V1. %GAlb declined between V1 and V2 (β = − 0.63% 95% CI [−0.8, −0.6] p < 0.001) and remained stable between V2 and PP (β = − 0.04% [−0.3, 0.2] p = 0.78). Body mass index (BMI) was inversely related to %GAlb in pregnancy (V1: rho = − 0.5, p = 0.0001; V2 rho = − 0.4, p = 0.006), but not PP (rho = − 0.15, p = 0.31). The longitudinal changes in %GAlb persisted after adjusting for BMI. Neither glycemia measurements nor hemoglobin A1c were associated with %GAlb at any time point, and adjustments for BMI did not reveal additional associations.Conclusion %GAlb decreases between early and late gestation and remains decreased PP, despite a PP increase in total albumin above early pregnancy values. Given the lack of correlation with OGTT values or A1c, %GAlb is unlikely to be useful in assessing glycemia in pregnant or PP women.Key Points
Keywords: gestational diabetes; gestational glycemia; glycated albumin; pregnancy biomarkers; postpartum diabetes; postpartum screening